Effect of single and combined exposures to UV-C and UV-A LEDs on the inactivation of Klebsiella pneumoniae and Escherichia coli in water disinfection - María-Angélica Galezzo (IWA Publishing, 2021)
A system consisting of one UV-A (365 nm) and two UV-C (265 nm) light-emitting diodes (LEDs) was built to evaluate the effect of single and combined exposures to UV-A and UV-C LEDs on Klebsiella pneumoniae and Escherichia coli inactivation and subsequent reactivation. The dose was measured by actinometry using potassium ferrioxalate. Of laboratory prepared samples, 10 mL were irradiated for 20, 30, 45, 60 and 90 s. Logarithmic inactivation and percentages of photoreactivation and dark repair were calculated. E. coli and K. pneumoniae were reduced by more than 7 and 4 logs, respectively, at a dose of 21.5 mJ cm−2 using UV-C. No positive synergistic effect on the inactivation of the two bacteria was observed when using a simultaneous combination of UV-C and UV-A, probably due to a reactivation of the bacteria in the presence of UV-A light, which was not observed in irradiated samples under an individual exposure of 265 nm. For E. coli under 265 nm, the percentage of photoreactivation amounted to 10%, 3 h after irradiation. The results of this study demonstrated the capacity to inactivate E. coli and K. pneumoniae up to a considerable level and provide information for the application of UV LEDs in point-of-use systems. HIGHLIGHTS kD was calculated for K. pneumoniae, under exposure to 265 nm UV light-emitting diode (LEDs).; K. pneumoniae is more resistant than E. coli under 265 nm exposition.; 265, 365 and 265/365 nm were effective to inactivate E. coli and K. pneumoniae.; No positive synergistic effect for inactivation from the 265/365 nm LED combinations.; Photoreactivation was the dominant mechanism of reactivation of E. coli.;